Role of ABA in the adaptive response of Arabidopsis plants to long-term boron toxicity treatment - Martínez-Mazón, Paula (Plant physiology and biochemistry : PPB, 2023)
Copyright © 2023 The Authors. Published by Elsevier Masson SAS.. All rights reserved.